Case Report: Successful Management of Post-Thymectomy Myasthenia Gravis with Septic Pneumonia Using Therapeutic Plasma Exchange (TPE) - Erwinsyah Erwinsyah; I Gusti Ngurah Mahaalit Aribawa; Cynthia Dewi Sinardja (Green Publisher Indonesia, 2026)
The incidence of infectious complications, particularly pneumonia, in patients with myasthenia gravis (MG) occurs in 30–50% of cases after thymectomy, often leading to prolonged mechanical ventilation. In 78.3% of MG cases, the administration of therapeutic plasma exchange (TPE) has been shown to improve neuromuscular function and reduce the need for postoperative mechanical ventilation, including complications such as septic pneumonia. A 36-year-old male with MGFA class IIIB and type AB thymoma presented with diplopia, ptosis, dysphagia, and limb weakness, and developed septic pneumonia following thymectomy. He required 21 days of ICU care and received five TPE sessions using a regimen of 5% human albumin and 0.9% normal saline, with a volume of 3,500 mL per session administered every three days. The primary goals of postoperative management in MG patients following thymectomy are to reduce dependence on mechanical ventilation and prevent complications such as myasthenic crisis and infection. Post-thymectomy TPE, when combined with supportive therapy including optimal fluid management, has been shown to provide significant clinical improvement, reduce the duration of mechanical ventilation, and lower the risk of postoperative complications. These findings are consistent with the management strategies and studies reported by Myllynen C, Prakash S, and Dogra S. Post-thymectomy TPE has been demonstrated to reduce mechanical ventilation dependence, decrease postoperative complications, and improve neuromuscular function in patients with MG.